The Evolution and Functioning of the Traded Gas Market in Britain - Heather, P (Oxford Institute for Energy Studies, 2010)
In this paper, we examine the evolution and functioning of the traded gas market in Great Britain.1 We will begin by looking at the historical background and the reasons why a successful liberalised gas market was able to develop in Britain. We will look at the Network Code and the National Balancing Point and examine their importance in facilitating an efficient wholesale market, effective balancing and nominations, before turning our attention to how the traded market actually functions. We will examine natural gas as a physical and as a traded commodity, analyse the market structure, (supply, demand and liquidity), explain the different routes to market, and the contractual documentation needed to trade. We will review the price drivers in the British market, looking at the three main phases of the bilateral contracts, contract indexation and the role of LNG and other commodities in natural gas pricing, culminating in a review of the trading dynamics in Britain and in Europe. Finally, we will examine the commercial prospects for the British gas market as it transitions from the 2000s to the 2010s and beyond in a changing global gas environment.